PENGEMBANGAN BUKU TEKS PERADABAN TRANSPORTASI LAUT BERBASIS PROJECT BASED LERANING SEBAGAI STRATEGI PENDIDIKAN KARAKTER RASA INGIN TAHU ANAK - Safitri, Destri; Ari Nugrahanta, Gregorius (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of active engagement and exploratory capacity among elementary school students in conventional, teacher-centered learning environments poses a significant obstacle to early childhood character building. This research focuses on developing a maritime transportation civilization textbook integrated with Project-Based Learning (PjBL) via a genetic approach, employing the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model to foster children's curiosity character. The research subjects involved 55 fourth-grade students at a public elementary school in Sleman Regency, Yogyakarta, divided into an experimental group (class IV A) and a control group (class IV B). The developed product was implemented through five maritime-themed project activities: constructing miniature ships using recycled cans, ice cream sticks, straws, used bottles, and cardboard. Based on the findings, the developed textbook achieved an average expert validation score of 3.78, categorized as "Excellent," thereby being declared highly feasible for use without requiring revisions. Furthermore, the quasi-experimental results demonstrated that the textbook effectively enhanced the experimental group's curiosity character, yielding an N-Gain score of 66.23% (moderate/moderately effective category), which significantly outperformed the control group. The z-score analysis indicated a substantial disparity in the specific indicators of "completing tasks to the point of losing track of time" (experimental 1.34 vs. control -1.45) and "engaging in conversations with strangers out of fascination" (experimental 1.2 vs. control -1.3). A high level of inter-rater reliability was confirmed by the overall mean Krippendorff's Alpha score of $α = 0.678$ (high category). These findings demonstrate that integrating PjBL with a maritime civilization theme successfully triggers substantial intrinsic motivation, deep focus, and explorative behavior in children.